Associations of circulation levels of cytokines with birthweight, preterm birth, spontaneous miscarriages, and stillbirth: A Mendelian randomization analysis - Wang, Honghong; Jiang, Jinghang; Jin, Tingwei; Wang, Yifu; Li, Mingli; Huang, Shengzhu; Xie, Juanjuan; Chen, Zhongyuan; Guo, Yi; Zheng, Jie; Jiang, Yonghua; Mo, Zengnan (Frontiers in Genetics, 2023)
Background: The association between immune imbalances and adverse pregnancy outcomes has been extensive investigated by observational studies, but remain unclear. Thus, this study aimed to establish the causality of the circulation levels of cytokines on adverse pregnancy outcomes, such as offspring’s birthweight (BW), preterm birth (PTB), spontaneous miscarriage (SM), and stillbirth (SB). Methods: Two-sample Mendelian randomization (MR) analysis was employed to investigate potential causal relations between 41 cytokines and pregnancy outcomes on the basis of previously published GWAS datasets. Multivariable MR (MVMR) analysis was implemented to investigate the effect of the composition of cytokine networks on the pregnancy outcomes. Potential risk factors were further estimated to explore the potential mediators. Results: Genetic correlation analysis based on large GWAS data sources revealed that genetically predicted MIP1b (β = −0.027, S.E. = 0.010, p = 0.009) and MCSF (β = −0.024, S.E. = 0.011, p = 0.029) were associated with reduced offspring’s BW, MCP1 (OR: 0.90, 95% CI: 0.83–0.97, p = 0.007) was associated with reduced SM risk, SCF (β = −0.014, S.E. = 0.005, p = 0.012) associated with decreased number of SB in MVMR. The univariable MR showed that GROa (OR: 0.92, 95% CI: 0.87–0.97, p = 0.004) was associated with decreased PTB risk. Except for the MCSF-BW association, all above associations surpassed the Bonferroni corrected threshold. The MVMR results revealed that MIF, SDF1a, MIP1b, MCSF and IP10 composed cytokine networks, associated with offspring’s BW. Risk factors analysis indicated that the above causal associations might be mediated by smoking behaviors. Conclusion: These findings suggest the causal associations of several cytokines with adverse pregnancy outcomes, which were potentially mediated by smoking and obesity. Some of the results did not been corrected through multiple tests and larger samples verification is required in further studies.